Lateral ovariohysterectomy in female cats: an alternative for birth control programmes - Mendoza-Estela, Jierson E. (2024)
Ovariohysterectomy through the linea alba is one of the most applied surgical techniques in companion animals; however, this technique presents frequent postoperative complications. The present study aims to demonstrate the feasibility and advantages of ovariohysterectomy in cats through the lateral approach. In total, 30 clinically healthy cats weighing 2.9 ± 0.9 kg body weight, 1.5- 4 years old and of various breeds, were operated on. In the preanesthetic medication, xylazine hydrochloride (0.1 mg/kg) and ketamine hydrochloride (0.5 mg/kg) were applied IM, anesthesia was done with diazepam (0.5 mg/kg) and ketamine hydrochloride (10 mg/kg). IV route, and maintenance with boluses of ketamine hydrochloride (0.5 mg/kg) based on dose-response. A single dose of amoxicillin (10 mg/kg) was applied IM at the end of surgery. The time of the surgical intervention was 19.8 ± 2.5 minutes and for wound healing it was 6.9 ± 1.2 days. Two patients 6.7% (2/30) presented inflammation and local infection. It is concluded that ovariohysterectomy through a lateral approach in cats is a viable alternative due to its ease of execution, reduced healing time and minimal presentation of postoperative complications.